Advisor's feedback as assessment practices in Doctoral Programs: a scoping review of empirical research - Liliana Silva; Massimo Marcuccio (Firenze University Press, 2019)
A theoretical framework based on the balanced assessment system proposes a definition of formative feedback within an interactionist context and supports the autonomy and active learning of the students involved. The scoping review aims at mapping characteristics of feedback provided by tutors with doctoral students, defining the level, degree, and method of delivery and the ability to promote active learning processes. For the identification and synthesis of the research 11.829 contributions were extracted from a query of different aggregators and databases (ProQuest, Scopus, Web of Science, EBSCO). From these, 24 contributions were included in the analysis by a text mining process following a selection of inclusion/exclusion and critical appraisal carried out by two researchers (K Cohen=0.70). From the analysis it is possible to highlight the prevalence of reinforcement feedback distributed during the development of the doctoral process. A need of training also emerges about assessment practices, such as feedback, to support self-assessment and autonomy of the student and to adopt computerized feedback models.   I feedback dei supervisori come pratiche di valutazione nei dottorati: una scoping review delle ricerche empiriche. Alla luce del quadro teorico basato sul sistema di valutazione bilanciata, è fornita una definizione delle caratteristiche del feedback formativo all'interno di un contesto interazionista e di sostegno all'autonomia e all'apprendimento attivo dei dottorandi coinvolti. La scoping review ha lo scopo di mappare le caratteristiche dei feedback forniti dai tutor ai dottorandi di ricerca, definendone il livello, il grado e le modalità di erogazione e la capacità di attivare processi di apprendimento attivo. Per l'identificazione e la sintesi della ricerca, 11.829 contributi sono stati estratti dalla query di diversi aggregatori e database (ProQuest, Scopus, Web of Science, EBSCO). 24 contributi sono stati inclusi nell'analisi per mezzo di un processo di text mining e a seguito di una selezione di criteri di inclusione/esclusione e valutazione critica svolta da due ricercatori (K Cohen=0.70). Dall'analisi, si evince la prevalenza di feedback di rinforzo durante lo sviluppo del processo di dottorato. Emerge l'esigenza di una formazione all'uso del feedback, per favorire un supporto ai processi di autovalutazione e all'uso di sistemi informatici.